The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.mayocp.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors and the Risk for Hospital-Acquired Clostridium difficile Infection

Abstract: The duration of PPI therapy is significantly associated with CDI. Clinicians should strongly consider restricting PPI use given the short exposure time associated with this increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 24 publications
(32 reference statements)
3
41
0
Order By: Relevance
“…Their high safety, efficacy and wide distribution lead to overuse, inappropriate dosage and excessive durations of treatment. Howell et al [15] reported that increasing levels of pharmacologic acid suppression are associated with increased risks of nosocomial Clostridium difficile (CD) infection and Barletta et al [16] reported that the duration of PPI therapy is significantly associated with CD infection and suggested consideration of restricting PPI use, given the short exposure time. However, more recent studies have offered conflicting viewpoints regarding the association between PPI use and increased risk of CD infection [17][18][19] .…”
Section: Terminologymentioning
confidence: 99%
“…Their high safety, efficacy and wide distribution lead to overuse, inappropriate dosage and excessive durations of treatment. Howell et al [15] reported that increasing levels of pharmacologic acid suppression are associated with increased risks of nosocomial Clostridium difficile (CD) infection and Barletta et al [16] reported that the duration of PPI therapy is significantly associated with CD infection and suggested consideration of restricting PPI use, given the short exposure time. However, more recent studies have offered conflicting viewpoints regarding the association between PPI use and increased risk of CD infection [17][18][19] .…”
Section: Terminologymentioning
confidence: 99%
“…Studies of this topic have been carried out in different countries [11][12][13]. However, few reports have focused on CDI in China.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies reported no increased risk of developing CDI if patients are exposed to a PPI . However, significantly more clinical studies found the use of a PPI among hospitalized patients as a risk factor for the development of CDI …”
Section: Discussionmentioning
confidence: 99%